Effect of Spiritual Care Program on Quality of Life in Patients with Heart Failure - farideh movahedi; Nasim Naderi; Fidan Shabani; Sepideh Taghavi; Rouhollah Mousavizadeh; Mahmood Sheikh Fathollahi (Mashhad University of Medical Sciences, 2021)
Background: Heart failure (HF) is the common result of most heart disorders. The quality of life (QoL) of these patients is severely impaired and they need continuous care. Spiritual care is a type of nursing care that may affect the QoL of patients.Aim: The present study aimed to determine the effect of spiritual care program on QoL in patients with HF.Method: This randomized controlled trial was performed at Rajaie Cardiovascular Medical and Research Center, Tehran, Iran in August 2020. In total, 84 patients were selected through convenient sampling and randomly assigned to two groups using block balanced randomization. Iranian Heart Failure Quality of Life (IHF-QoL) questionnaire and Parsian and Dunning spirituality questionnaire were complemented by the two groups before and after 1-month follow-up. The intervention was performed for the intervention group in two virtual educational sessions (each 1.5 h) as well as a 1-month follow-up three times a week for 1 h per session via WhatsApp. Finally, the data of 74 patients were analyzed using SPSS software (version 22). The significance level was considered at P < 0.05.Results: The groups were homogenous in terms of demographic characteristics. Dimensions of QoL in mental limitations (P<0.001) and self-care (P<0.01) were significant in the intervention group, compared to the control group. Therefore, the spiritual care program significantly increased the total score of QoL (P<0.01).Implications for Practice: Results of the study indicated that the spiritual care program greatly improved the total score of QoL and can be considered a part of the holistic care program.